Control freaks - Thomas, J. E. (Children's author) (Levine Querido, 2023)
Seventh-grader Frederick Douglass Zezzmer fits right in at competitive Benjamin Banneker College Prep school in Denver and has a fifty-seven-step plan for becoming the world's greatest inventor. Recently though, a few things have threatened to derail that plan. First, his birth father, a former professional football player, has reentered his life, and wants to expose him to a summer sports camp, something he dreads. Second, teams are forming for the golden B-B trophy team competition, which contains seven challenges to be completed over the course of one week and Frederick is paired with four misfits no one wants in their group. As Frederick navigates how to win the competition and avoid the sports camp, he learns valuable lessons in seeing others for who they are and the rewards of new experiences.